GR2L: A robust dual-layer green roof water balance model to assess multifunctionality aspects under climate variability - Knappe, Jan; van Afferden, Manfred; Friesen, Jan (Frontiers in Climate, 2023)
Urban blue-green infrastructures (BGIs) fulfill a variety of functions that enable cities to cope with climate change and additional urban anthropogenic pressures such as increasing population density, heat island effects, biodiversity loss, and progressive sealing of permeable surfaces. In the urban water cycle, BGIs can play an important role when it comes to both manage and mitigate the direct effects of ever increasing periods of extended drought as well as the temporary excess of stormwater during and after heavy rainfall events. Although in principle, BGIs are multifunctional, the individual infrastructure has to be designed and operated towards achieving a set of specific objectives, e.g. stormwater retention, infiltration, or storage for increased overall water resilience. In this study, we focus on green roofs as a key BGI for water resilient urban spaces. Green roofs have the advantage to unlock underutilized roof space for urban water management and additional co-functions, thus, not contributing to additional urban land use conflicts at ground level. Green roofs are available in a multitude of design types based on the selection of vegetation, the make and thickness of the substrate layer, and the absence or presence of additional retention space. With GR2L, we present a robust dual-layer green roof water balance model that is able to cope with a variety of design aspects and was validated and calibrated using a data set of four green roof types with varying technical specifications and different vegetation cover. Calibration results indicate that a green roof factor (based on the classic crop factor) largely depends on the retention capacity of green roofs making the results widely applicable in planning. We used the calibrated models to assess how different green roof types operate under variable climatic conditions using meteo ensembles that consist of dry and wet years as well as a suite of randomly selected years. The results provide information on how green roof designs can be optimized for fulfilling a given set of water balance driven multifunctionality objectives under varying climatic conditions and enable an assessment of the performance of existing green roof designs against these conditions.